Correlations among Corneal Biomechanical Parameters, Stiffness, and Thickness Measured Using Corvis ST and Pentacam in Patients with Ocular Hypertension - Qian Liu; Chenjiu Pang; Changgeng Liu; Wenjun Cheng; Shuai Ming; Wenwen Du; Xiaomei Feng (Journal of Ophthalmology)
Background. To preliminary explore the correlations among corneal biomechanical parameters, stiffness, and thickness in patients with ocular hypertension (OHT) before and after treatment with topical antiglaucoma medications. Methods. This was a retrospective study that included 35 eyes with newly diagnosed OHT. Axial length (AL), apical corneal thickness, and minimum corneal thickness were measured using Pentacam. The lengths, velocities, and times of the first and second corneal applanations (A1L, A1V, A1T, A2L, A2V, and A2T, respectively); the highest concavity radius; highest concavity peak distance (PDHC); highest concavity deformation amplitude (DAHC); highest concavity time (HCT); pachymetry (PACH); stress-strain index (SSI); stiffness parameter-A1 (SP-A1); deformation amplitude ratio (DA ratio); integrated radius (IR); Ambrosio’s relational thickness horizontal (ARTh); corneal biomechanical index; noncorrected intraocular pressure (IOPnct); and biomechanically corrected IOP (bIOP) values were measured using the corneal visualization Scheimpflug technology (Corvis ST/CST). Results. After 5 weeks of treatment, Goldman applanation tonometer-IOP, IOPnct, bIOP, PACH, A1T, A2V, SSI, SP-A1, and ARTh decreased, but A1V, A2T, PDHC, DAHC, DA ratio, and IR increased significantly (all p<0.05). SP-A1 and A1T were positively associated with premedication IOP and IOP changes, whereas A1V, A2T, PDHC, and IR were negatively associated (all p<0.05). DAHC and DA ratio had significantly negative correlations with IOP variations. PDHC was found to be positively correlated with AL (p<0.05). A positive relationship was noted between SP-A1 and HCT before medication (p<0.05). Conclusions. SP-A1 was significantly and consistently associated with IOP. HCT might be correlated with SP-A1. SP-A1 and CST parameters could serve as potential biomarkers for evaluating OHT treatment efficacy.